(NpROIZWEDENIQ ~AJKOWSKOGO (B. (NsTRUKTURNYJ ANALIZ(B.s (NmONOGRAFIQs - (N`(B. (Nn(B. (Nt@LIN(B.s ((NmOSKWAs (NmUZYKAs, 1973)
(Nw NASTOQ]EM IZDANII DAETSQ PODROBNYJ STRUKTURNYJ ANALIZ INSRUMENTALXNYH PROIZWEDENIJ KRUPNOJ FORMY ~AJKOWSKOGO(B.s
Keywords: (NMONOGRAFIQs